Kopiko Product Placement in Korean Drama on Brand Awareness - Alexandra Bella Ivena; El Chris Natalia (Communicare : Journal of Communication Studies, 2023)
Kopiko, one of the products of PT Mayora Indah Tbk appears as a product placement in the Korean drama "Hometown Cha-Cha-Cha". Kopiko is a coffee candy from Indonesia with the benefit of relieving drowsiness.  This research aims to determine the effect of Kopiko's product placement in the Korean drama "Hometown Cha-Cha-Cha" on the brand awareness of South Korean people who live in South Korea. The theory used in this research is Marketing Communication, Product Placement, and Brand Awareness. This research uses quantitative methods with visual dimension or screen placement, and plot connections for product placement variables. In addition, the dimensions of the top of mind, brand recall, brand recognition, and unaware of the brand for brand awareness variables. Data collection was carried out by distributing questionnaires online to 96 respondents. The sample selection used purposive sampling with the criteria of South Korean citizens living in South Korea and having watched the Korean drama “Hometown Cha-Cha-Cha”. The result of this research shows that there is a significant effect between Kopiko's product placement on the brand awareness of South Korean people.